1991
DOI: 10.1159/000133133
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal assignments of 23 biochemical loci of the rat by using rat × mouse somatic cell hybrids

Abstract: A panel of 18 rat × mouse somatic cell hybrid clones segregating individual rat chromosomes in different combinations was used to assign 23 biochemical loci to rat chromosomes. The chromosomal locations for these 23 loci were determined as follows: GOT1 on rat chromosome 1; HAGH on 2; ACP2, ADA, GANC, ITPA, and SORD on 3; LDHB on 4; PEPB on 7; GLB1 and HEXA on 8; IDH1 on 9; UMPH2 on 10; GUSB on 12; FH and PEPC on 13; PEPS on 14; ESD and NP on 15; DIA4 on 19; and PP on 20. In addition, ACPI and GLOl were reassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…A panel of 18 ratimouse SCHs [32] was kindly made available to us by Professor T. Serikawa (Institute of Laboratory Animals, Kyoto University, Kyoto, Japan). From the rat and mouse fetuin-B cDNAs (see the Results section), an oligonucleotide pair that would favour an amplification of the corresponding rat cDNA was designed with the following conditions : amplified area to be located in the 3h-non-coding sequence of the cDNAs ; a 100 % match between the oligonucleotides and the rat cDNA ; a high number of mismatches in each oligonucleotides versus the mouse fetuin-B cDNA ; amplicon size in the 200-bp range ; and T m in the 56-60 mC range.…”
Section: Rat Gene Assignment With a Panel Of Ratimouse Somatic Cell Hmentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 18 ratimouse SCHs [32] was kindly made available to us by Professor T. Serikawa (Institute of Laboratory Animals, Kyoto University, Kyoto, Japan). From the rat and mouse fetuin-B cDNAs (see the Results section), an oligonucleotide pair that would favour an amplification of the corresponding rat cDNA was designed with the following conditions : amplified area to be located in the 3h-non-coding sequence of the cDNAs ; a 100 % match between the oligonucleotides and the rat cDNA ; a high number of mismatches in each oligonucleotides versus the mouse fetuin-B cDNA ; amplicon size in the 200-bp range ; and T m in the 56-60 mC range.…”
Section: Rat Gene Assignment With a Panel Of Ratimouse Somatic Cell Hmentioning
confidence: 99%
“…This allowed for chromosomal assignment of the rat fetuin-B gene from a panel of 18 ratimouse SCHs. Indeed, the distributions of rat chromosomes in these 18 hybrids [32] versus the distribution of a rat fetuin-B gene amplicon in the same hybrids (Table 3) allowed us to assign the fetuin-B gene to Rattus nor egicus chromosome 4 (RNO4).…”
Section: Table 1 Hepatic Levels Of Fetuin-a and Fetuin-b Mrnas As A Fmentioning
confidence: 99%
“…1991). Karyotype and isozyme analyses to determine the rat chromosome content of the hybrid cell lines were carried out on the cells from which the DNAs were prepared (Yasue et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…In the light of the more precise map position of Tscc1 determined in this study, one of the candidate genes for Tscc1 is NQO1 (the gene for quinone oxidoreductase, synonymous with DT-diaphorase or NADH-cytochrome b 5 reductase). 17,18) Quinone oxidoreductase is one of the major enzymes that converts 4NQO to the more active metabolite, 4-hydroxyaminoquinoline 1-oxide (4HAQO). 19,20) Our preliminary study showed that the enzyme activity is higher in DA than in WF rats.…”
Section: )mentioning
confidence: 99%